Design Exploration of Bamboo Micro House using Hyperbolic Paraboloid Structure - Nareswarananindya Nareswarananindya; Sigit Hadi Laksono; Annisa Nur Ramadhani (Journal of Civil Engineering, Planning and Design, 2022)
Limited land is a major problem in big cities, which has a direct impact on increasing land prices and low level of affordability. Micro house concept can be a solution to this problem. Planning a bamboo micro house with local materials can be an effort to contribute to a sustainability agenda. Bamboo is a local material that is environmentally friendly, adaptive, and widely available in Indonesia. Preserved bamboo construction with certain treatments is also affordable and durable for its high sustainability impact. This paper aims to study the exploration of bamboo materials in designing micro houses that suit the needs of urban communities. The house concept is open plan, so the spaces can be used multi-functionally by taking into account the requirements of livable micro houses. The method used is the Cyclical Design Process which consists of three stages, which are analysis stage, synthesis stage, and evaluation stage which is carried out repeatedly to produce a design that is in accordance with the design criteria that have been determined. Paraboloid hyperbolic structure system is used to produce an attractive and efficient form. The development of this micro-bamboo house is expected to be useful in solving the backlog and housing affordability problems in Indonesia.